“TYPES OF SPEECH SKILLS IN A FOREIGN LANGUAGE” (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
This article explores the methodological foundations of teaching vocabulary in a foreign language, emphasizing both linguistic and psychological aspects of word acquisition. It examines the dual nature of the word—its emotional (external) and semantic (internal) components—and explains how concepts are formed through logical processes such as comparison, analysis, abstraction, synthesis, and generalization. The study outlines the two-stage methodology of vocabulary instruction: the static stage, which includes selecting, organizing, and classifying lexical units for textbooks, and the dynamic stage, which focuses on developing learners’ lexical skills. Special attention is given to methodical selection, where lexical minimums are created based on scientific criteria, and to the distribution of vocabulary into active/passive and reproductive/receptive categories.